Performativity(ies) of memory(ies) interdisciplinary conference : book of abstracts - Dinis, Frederico (Ed.) (2025)
Da apresentação "This publication gathers the contributions of scholars, researchers, and artists from around the world whose work engages with the complex, mutable, and deeply human intersections between performativity and memory. It serves not only as a record of the conference but also as a demonstration to the growing relevance of these fields within contemporary cultural, artistic, and theoretical inquiry."